Jaundice in pregnancy: a clinical study at JSS hospital, Mysore - Kondareddy, Triveni; KA, Krithika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Jaundice in pregnancy is an important medical disorder seen more often in developing countries than in developed ones. It could be peculiar to the pregnancy viz., acute fatty liver of pregnancy, recurrent cholestatic jaundice in pregnancy and jaundice complicating toxemia of pregnancy. It can be concurrent with pregnancy such as due to infective pathology like viral hepatitis or due to gallstones or other causes. Jaundice in pregnancy carries a grave prognosis for both the fetus and the mother, and is responsible for 10% of maternal deaths. The present study analyzes the causes and the fetomaternal outcome in pregnancies affected with jaundice. Methods: An analysis of fetomaternal outcome of 15 pregnant women admitted with jaundice during August 2014 to September 2015 is made. Results: The incidence of jaundice in our study is 0.39/1000 deliveries, with the disease more common in younger age group. Majorities are unbooked and were in their third trimester of pregnancy. Viral hepatitis found to be the commonest cause. Perinatal mortality was 25% and prematurity accounted for majority of deaths. Maternal mortality was 20%. Main Causes of death was hepatic encephalopathy with renal failure, disseminated intravascular coagulation, postpartum hemorrhage and sepsis. Conclusions: Jaundice and pregnancy is a deadly combination resulting in a very high perinatal as well as maternal morbidity and mortality, and requires an early diagnosis and careful management.